The Analysis of Turkey's Freight Transport in Terms of Tranport Modes - Senay Oguztimur; Kenan Colak (European Regional Science Association (ERSA), 2013)
Turkey enjoys a strategic location, with the potential to play a pivotal role in regional and global integration. The important energy, trade and transport networks which connect west to east and north to south are keys to unleashing this potential. Recent economic and political developments throughout neighbouring regions -the Balkans, the Black Sea, the Mediterranean Basin, the Caucasus, Central Asia and the Middle East- have further emphasized Turkey?s role. A dynamic logistics industry, combined with a large international road vehicle fleet, underscores Turkey?s potential to become one of the most significant logistics hubs and transit countries in the region. Yet, some 96 % of passengers and 92 % of freight are transported by road in Turkey. This dependence on road transport creates imbalance in favour of road transport. Indications such as congestion, environmental downsides, border-crossing problems, road taxation, restrictions on road traffic, permit shortages and customs constraints are some examples. The changing context of international transport has prompted Turkish international road hauliers to adopt innovative solutions to expand their intermodal fleets and develop new Roll-On Roll-Off (RO-RO) lines between Turkey and several European ports. At present, these solutions typically combine road, sea and RO-RO and Rolling Road (Rollende Landstrase/Ro-La) transport. In order to overcome this vulnerability and become more sustainable, Turkey needs to develop intermodal transport solutions that can rapidly yield results without losing the advantages of its competitive road transport system. On the other hand, Turkey has significant potential, and several projects are underway to develop intermodal transport. Among these are the Kars-Tbilisi project, Marmaray Project, Mersin Container port project, and Çandarlý and Filyos port projects. The aim of this paper is to focus on the developments and challenges which Turkey have to face in order to enrich its operating capability of intermodal transport, whether as road-rail, Ro-La, RO-RO and rail ferry services in its international transport and logistics activities, the country still needs a comprehensive intermodal strategy and framework. In other words, a study is done which would allow a more efficient and sustainable growth of intermodal operations. The authors also make recommendations that are considered necessary to further promote and improve intermodality in Turkey.
Keywords: R40; R41; 330; transport; networks; Turkey